Euthanasia Ditinjau dari Aspek Medis, Bioetik, dan Hukum - I Gede Eka Agung Agastya Punia (Jurnal Hukum dan Etika Kesehatan, 2024)
Euthanasia is the application or cessation of procedures that allow the acceleration or triggering of the death of patients whose illness cannot be cured, in order to free them from the extraordinary suffering that torments the patient. types of euthanasia can be divided into 2 types. They are active euthanasia and passive euthanasia. Active euthanasia is an event where a doctor or other health professional intentionally performs an act to end the life of a patient. Passive euthanasia means stopping or withdrawing any action or treatment needed to maintain the continuity of human life. This research is a normative research using conceptual and statutory approaches. The results of the research found that in the medical aspect it was found that drugs are used in active euthanasia and pseudoeuthanasia is a practice that resembles passive euthanasia. Based on the Bioethical aspect, Autonomy and Justice play an important role in euthanasia decision making and on the legal aspect. Until now there is no Indonesian law that regulates the "right to die". The closest article for active euthanasia cases is article 344 of the Criminal Code and Law No. 17 of 2023 on Health can be the basis for passive euthanasia cases in Indonesia.